Incidence, short-term outcome, and spatial distribution of stroke patients in Ludhiana, India. (2nd February 2016) - Pandian, Jeyaraj D.; Singh, Gagandeep; Kaur, Paramdeep; Bansal, Rajinder; Paul, Birinder S.; Singla, Monika; Singh, Shavinder; Samuel, Clarence J.; Verma, Shweta J.; Moodbidri, Premjeeth; Mehmi, Gagandeep; Sharma, Amber; et al.
Abstract : Objective: To estimate the incidence, short-term outcome, and spatial distribution of stroke patients and to evaluate the completeness of case ascertainment in Ludhiana. Methods: This population-based prospective cohort study was conducted in Ludhiana, Punjab, Northwest India. All first-ever stroke patients (≥18 years) were included between March 2010 and March 2013 using WHO Stepwise Approach Surveillance methodology from the city. Stroke patient data were obtained from hospitals, scan centers, and general practitioners, and details of deaths from the Municipal Corporation. Results: Out of 7, 199 stroke patients recruited, 3, 441 were included in final analysis. The mean age was 59 ± 15 years. The annual incidence rate was 140/100, 000 (95% confidence interval [CI] 133–147) and age-adjusted incidence rate was 130/100, 000 (95% CI 123–137). The annual incidence rate for stroke in the young (18–49 years) was 46/100, 000 (95% CI 41–51). The case fatality at 28 days was 22%. Patients above 60 years of age ( p = 0.03) and patients who were managed in public hospitals had poor survival ( p = 0.01). Hot spots for cumulative incidence were seen in central and southern parts of the city, and hot spots for poor outcome were seen in the outskirts of the city. Conclusions: The incidence rates are similar to other studies from India. Stroke patient survival is poor in public hospitals. The finding of spatial analysis is of public health significance for stroke prevention and strengthening of stroke services.